2021
DOI: 10.1177/00938548211003117
|View full text |Cite|
|
Sign up to set email alerts
|

Trauma-Informed Interventions for At-Risk and Justice-Involved Youth: A Meta-Analysis

Abstract: The impact of trauma on children and youth has potentially serious and long-lasting negative consequences, including increased involvement in the juvenile and criminal justice systems. The objective of this study was to meta-analyze research on the effectiveness of trauma-informed treatment programs for justice-involved youth and youth at risk of justice system involvement who have experienced some form of trauma. Our systematic search identified 29 publications that met our eligibility criteria and represent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
0
12
0
Order By: Relevance
“…Critical findings and broad implications for implementation are shown in Tables 1 and 2. Collectively, trauma‐informed interventions appear to be promising for improving mental health symptoms and behavior in JIY (Olaghere et al, 2021). However, many gaps exist in our understanding of trauma‐informed care with JIY specifically or implementation within the juvenile justice setting in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Critical findings and broad implications for implementation are shown in Tables 1 and 2. Collectively, trauma‐informed interventions appear to be promising for improving mental health symptoms and behavior in JIY (Olaghere et al, 2021). However, many gaps exist in our understanding of trauma‐informed care with JIY specifically or implementation within the juvenile justice setting in general.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a handful of these interventions have been systematically evaluated for JIY. Olaghere et al (2021) recently conducted a meta-analysis of trauma-focused interventions for JIY and youth at-risk for justice involvement. The study reported encouraging results from cognitive-behavioral-based therapies (CBT).…”
mentioning
confidence: 99%
“…Several systematic reviews and meta-analyses have examined the effectiveness of traumaspecific interventions for juveniles without CLS involvement (Cohen & Mannarino 2015, de Arellano et al 2014) and for those with CLS involvement (Ford et al 2016, Han et al 2021, Zettler 2021. The two most recent systematic reviews examined experimental and quasi-experimental studies targeting CLS-involved juveniles and found small to null effects regarding the reduction of mental health symptoms and null effects on engagement in delinquency (Olaghere et al 2021, Rhoden et al 2019. These reviews coalesce around the efficacy of eye movement desensitization and reprocessing therapy and cognitive behavior therapy (CBT) as promising categories of interventions, with the strongest evidence for trauma-focused CBT ( Jensen et al 2017).…”
Section: Trauma-informed Carementioning
confidence: 99%
“…Levenson describes traumainformed social work practice as focused on safety, trust, collaboration, choice, and empowerment. 30 Specific interventions used in delinquency programs include Trauma and Grief Components Therapy for Adolescents (TGCTA), Cognitive Processing Therapy (CPT), Trauma-Adapted Multidimensional Treatment Foster Care (TA-MTFC), the Attitudes Related to Trauma-Informed Care (ARTIC) questionnaire, the Think Trauma Curriculum, the Sanctuary Model, and Trauma Affect Regulation Guide for Education and Therapy (TARGET), 31 cognitive behavior therapy, 32 Trauma Recovery and Empowerment, and Seeking Safety. 33 In general, these are therapeutic models administered by a mental health professionals trained in trauma, its effects, and specific treatment approaches.…”
Section: Defining and Measuring Traumamentioning
confidence: 99%